2014
DOI: 10.1002/jrs.4583
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopy and ancient ceramics: applications and problems

Abstract: Micro-Raman spectroscopy is applied for the study of two classes of ancient ceramic artefacts showing different features and technological background, i.e. the fine-grain Black Gloss Ware from Motya (Sicily, Italy) and the coarse-grain pottery from Khirbet al-Batrawy (Jordan). The characterization of the mineralogical composition of these ceramics allows exploring the firing conditions and the manufacturing process. In particular, μ-Raman spectroscopy permits to define the mineralogical assemblage of the bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 57 publications
0
28
0
1
Order By: Relevance
“…In addition, it is needful to explore how the vessels were formed and decorated on the surface and their conditions of firing [20,39,40].…”
Section: Production Technology and Provenance Of Raw Materialsmentioning
confidence: 99%
“…In addition, it is needful to explore how the vessels were formed and decorated on the surface and their conditions of firing [20,39,40].…”
Section: Production Technology and Provenance Of Raw Materialsmentioning
confidence: 99%
“…Previous studies by photoacoustic spectroscopy in Aztec ceramics from 1325 to 1521 AD revealed an absorption peak around 530 nm characteristic of earth sienna pigment (Fe 2 O 3 · (n H 2 O) + MnO 2 · (n H 2 O) + Al 2 O 3 ). This study was carried out in combination with EDS technique Spectrochimica Acta Part B 119 (2016) [10][11][12][13][14][15][16] that confirmed the presence of iron in the pigment under analysis [5]. Other analytical studies were carried out on Maya ceramics from Guatemala and Honduras neighbouring countries, but none has been conducted on Tarascan ceramics [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of organic and inorganic pigments is the dominant issue in the ceramic analysis using Raman spectroscopy. This technique allows the identification of crystalline and amorphous compounds, and the discrimination of the mineral phases without the interference of matrix signal [6,[12][13][14]. Nevertheless the fluorescence effect in Raman spectroscopy may hamper the identification of the pigments characteristic bands and in these cases XRD could represent a good complementary tool although limited to the identification of crystalline compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the pigments used for ceramic glazes in soft paste, hard paste and majolica ceramics have been the subjects of numerous articles and are extensively reviewed elsewhere [68,84,86,87,90,125,258]. For the ceramic paste, the identification of mineral phases, especially in traces, offers a more detailed characterisation of the mineralogical assemblage, leading to the identification of the raw materials used, which can then contribute to illuminating clues about their provenance [204]. Additionally, the characterisation of the mineralogical composition reveals clues to the firing conditions (temperatures reached, firing atmosphere) to document the manufacturing process.…”
Section: Ceramicsmentioning
confidence: 99%